1988
DOI: 10.1084/jem.168.6.1953
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CD4 membrane expression and CD4 mRNA during acute human immunodeficiency virus replication.

Abstract: Using mAbs and genomic probe to the CD4 molecule, the HIV receptor, we demonstrated that HIV replication induces the disappearance of its functional receptor from the cell surface by two distinct mechanisms. First, after being expressed onto the cell surface, HIV envelope gp110 will complex CD4, efficiently masking the CD4 epitope used by the virus to bind its receptor. This phenomenon occurs on the surface of each infected cell and is not due to the release of soluble gp110; infection with recombinant HIV/vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
43
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 44 publications
7
43
0
Order By: Relevance
“…These T cells constitute a minority of CD4 ϩ T cells (5,22), and therefore, the 50% depletion of the cells observed in our experiments did not translate into a significant depletion of the total numbers of CD4 ϩ T lymphocytes. We found that depletion of CD4 ϩ CCR5 ϩ cells was accompanied not only by downregulation of CD4, observed earlier in other systems (26,45), but also by downregulation of CCR5. Coreceptor downregulation was reported earlier for CXCR4 (14,57,59) and has recently been reported for CCR5 (8,59) also.…”
Section: Discussionsupporting
confidence: 81%
“…These T cells constitute a minority of CD4 ϩ T cells (5,22), and therefore, the 50% depletion of the cells observed in our experiments did not translate into a significant depletion of the total numbers of CD4 ϩ T lymphocytes. We found that depletion of CD4 ϩ CCR5 ϩ cells was accompanied not only by downregulation of CD4, observed earlier in other systems (26,45), but also by downregulation of CCR5. Coreceptor downregulation was reported earlier for CXCR4 (14,57,59) and has recently been reported for CCR5 (8,59) also.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is similar to the situation for cells chronically infected by avian retroviruses (13,14) and reflects an important cellular adaptation to infection that facilitates establishment of virus persistence. HIV-1-infected cells are known to have decreased numbers of surface CD4 receptors (38)(39)(40)(41) and similar observations have been made for HCEM cells (not shown) . Reduced receptor levels appear to be a key alteration in this cell line that decreases reinfection rates .…”
Section: Discussionsupporting
confidence: 66%
“…Once inside the cell, the genetic material of the virus directs rapid and sustained downregulation of CD4 (26,62), a phenomenon that promotes viral spread by preventing superinfection, enabling the release of progeny virions, and interfering with the host immune response (3,6,34,53). The ability of HIV-1 to downregulate CD4 depends on two accessory proteins encoded in the viral genome, Nef and Vpu (32,38,45,61).…”
mentioning
confidence: 99%